2004
DOI: 10.1200/jco.2004.02.052
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Risk in Cancer Patients From 1960 to 1999

Abstract: Cancer may be a risk factor for suicide, particularly shortly after diagnosis. However, the relative risk gradually decreased during the period 1960 to 1999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
140
5
14

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(191 citation statements)
references
References 31 publications
24
140
5
14
Order By: Relevance
“…Urban et al9 found that suicide has not changed significantly decreased in lung cancer over time. However, in contrast to rising suicide rate of US general population, the suicide mortality rate of NSCLC patients has decreased considerably over past decades, which is consistent with previous study about suicide trend among cancer patients 12, 13, 14. This result may be associated with relatively better prognosis of NSCLC, because of early screening test for lung cancer and significant advances in treatment, such as chemotherapy and targeted therapy 15, 16, 17…”
Section: Discussionsupporting
confidence: 81%
“…Urban et al9 found that suicide has not changed significantly decreased in lung cancer over time. However, in contrast to rising suicide rate of US general population, the suicide mortality rate of NSCLC patients has decreased considerably over past decades, which is consistent with previous study about suicide trend among cancer patients 12, 13, 14. This result may be associated with relatively better prognosis of NSCLC, because of early screening test for lung cancer and significant advances in treatment, such as chemotherapy and targeted therapy 15, 16, 17…”
Section: Discussionsupporting
confidence: 81%
“…An increased incidence of suicide in cancer patients compared with the general public has been demonstrated by several studies [8][9][10][11][12]14,15,17 . Specific tumour sites associated with the highest risk of suicide include lung 22 , stomach 17 and oral cavity 23 .…”
Section: Discussionmentioning
confidence: 99%
“…A potential explanation for that finding could be related to the timing of suicide. The risk of suicide is felt to be strongest very early after diagnosis [14][15][16]33 . Fang et al 15 found that the highest risk fell within the first 12 weeks after diagnosis (relative risk: 4.7) and that the risk lessened after that time (relative risk at 12-52 weeks: 2.1; relative risk at 52 weeks and beyond: 1.6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For several years after a cancer diagnosis, the suicide rate is higher for patients than for the general population, and evidence that cancer increases suicide risk has been accumulating in the United States (1, 2), Norway (2, 3), Sweden (2,4), Austria (2,5), Finland (2), and Denmark (1)(2)(3)(4)(5)(6). The number of people who live with the aftereffects of cancer and its treatment-disability, fear of recurrence, and economic burden-is growing (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%